2007
DOI: 10.3892/ijo.31.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

X-chromosomal inactivation analysis of uterine leiomyomas reveals a common clonal origin of different tumor nodules in some multiple leiomyomas

Abstract: Uterine leiomyomas were shown to be clonal lesions, but the relationship among different tumor nodules in multiple uterine leiomyomas remains unresolved. In this study, X-chromosomal inactivation patterns of these tumor nodules were shown by allelic polymorphism analysis through polymerase-chain reaction at the phosphoglycerate kinase and androgen receptor loci following pretreatment with the methylation-sensitive restriction enzyme HpaII or HhaI. A total number of 113 cases of uterine leiomyomas were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
2
8
0
1
Order By: Relevance
“…We demonstrated that fibroids within the same woman often have different growth rates despite having a similar hormonal milieu. Indeed, each tumor appeared to have its own intrinsic growth rate, consistent with studies showing that fibroids are monoclonal in origin (15,16) with variable molecular characteristics (17)(18)(19)(20)(21). The only other large study of fibroid growth was conducted in Japan, and most of the 70 participants had only a single tumor (11); thus, variation in growth of fibroids from the same woman could not be evaluated.…”
Section: Discussionsupporting
confidence: 54%
“…We demonstrated that fibroids within the same woman often have different growth rates despite having a similar hormonal milieu. Indeed, each tumor appeared to have its own intrinsic growth rate, consistent with studies showing that fibroids are monoclonal in origin (15,16) with variable molecular characteristics (17)(18)(19)(20)(21). The only other large study of fibroid growth was conducted in Japan, and most of the 70 participants had only a single tumor (11); thus, variation in growth of fibroids from the same woman could not be evaluated.…”
Section: Discussionsupporting
confidence: 54%
“…Several genetic studies based on the unique isoenzyme pattern (7, 8), X-inactivation (9, 10) and DNA methylation-sensitive HUMARA assay (11) have demonstrated that uterine fibroids are monoclonal in origin. Accordingly, some studies have proposed that these benign tumors could originate from a single dysregulated myometrial smooth muscle stem cell, under the influence of ovarian hormones (6, 12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Human uterine fibroids are clonal in origin, as confirmed by studying the inactivation of heterozygous-status alleles on the X chromosome [11]. Additionally, recent studies have confirmed that the different cell types contained in fibroids (mainly smooth muscle cells and fibroblasts) are all clonally derived from a parental cell with implied multipotent stem cell properties [12].…”
Section: Cellular Origin Of Fibroids: Candidate Cells For the Developmentioning
confidence: 88%
“…Moreover, the introduction of let-7 microRNA in cultures of cells from these large myomas (with relative HMGA2 overexpression) resulted in a reduction of HMGA2 protein. However, it is hard to imagine that in vivo regulation of HMGA2 by let-7 has a specific functional role in fibroids or is the only factor contributing to tumor genesis and growth [11,31].…”
Section: Translocation T(12;14) (Q14-15;q23-24) Hmga2 and Rad5ibmentioning
confidence: 99%